Surface Grafted Polymer Brushes: Potential Applications in Textile Engineering (Journal of Fiber Bioengineering and Informatics, 2018)
Polymer brushes are assemblies of macromolecules that are tethered by one end to a surfaceor interface. The advantage of polymer brushes over other surface modification methods (e.g. selfassembledmonolayers) is their mechanical and chemical robustness, coupled with a high degreeof synthetic flexibility towards the introduction of a variety of functional groups. In this paper, anoverview of the representative synthesis method of polymer brushes is presented and their potentialapplications on smart surfaces, wettability and biocompatible surfaces are explored. Their potentialapplications in textile engineering are discussed.
Keywords: polymer brush; surface-initiated polymerization; bio-compatible surface; patterned brush; smart surface